Exposure–Response Analyses for Therapeutic Dose Selection of Belantamab Mafodotin in Patients With Relapsed/Refractory Multiple Myeloma. Issue 5 (4th October 2021) - Ferron‐Brady, Geraldine; Rathi, Chetan; Collins, Jon; Struemper, Herbert; Opalinska, Joanna; Visser, Sandra; Jewell, Roxanne C.
Abstract : Belantamab mafodotin is an antibody–drug conjugate comprising a humanized anti‐B‐cell maturation antigen (BCMA) monoclonal antibody conjugated to monomethyl auristatin F (MMAF) via a protease‐resistant maleimidocaproyl linker. Single‐agent belantamab mafodotin showed clinically meaningful activity and manageable safety in patients with heavily pretreated relapsed/refractory multiple myeloma (RRMM) in the phase I DREAMM‐1 and phase II DREAMM‐2 studies and is approved by the US Food and Drug Administration and European Medicines Agency for RRMM treatment. To support monotherapy dose selection, the relationship between Cycle 1 exposure (derived using a population pharmacokinetic model) and clinical response (for multiple efficacy and safety end points) was explored. In DREAMM‐2, efficacy end points (probability of response (PoR) and progression‐free survival (PFS)) were associated with exposure in univariate evaluation; however, once disease burden factors were included in the model (e.g., baseline soluble BCMA, ß2 ‐microglobulin), exposure was no longer significant. Patients with higher disease burden had lower exposure. In DREAMM‐1, belantamab mafodotin exposure was the only variable to correlate with PoR and PFS. Probability of corneal events (keratopathy), but not dry eye or blurred vision, was strongly associated with belantamab mafodotin exposure (DREAMM‐2). Higher cys‐mcMMAF maximum plasma drug concentration (Cmax ) and lower baseline platelet count were associated with increased probability of thrombocytopenia (DREAMM‐1 and DREAMM ‐2). In general, safety end points were more strongly associated with belantamab mafodotin exposure than efficacy end points, particularly after disease factors and patient characteristics were taken into account. Overall, these findings supported the monotherapy dose recommendation of belantamab mafodotin as 2.5 mg/kg every 3 weeks in patients with RRMM who have received four or more prior therapies.